Occurrence of Virulence Genes Associated with Diarrheagenic Pathotypes in Escherichia coli Isolates from Surface Water - Sidhu, Jatinder P. S. (American Society for Microbiology, 2013)
Escherichia coli isolates (n = 300) collected from six sites in subtropical Brisbane, Australia, prior to and after storm events were tested for the presence of 11 virulence genes (VGs) specific to diarrheagenic pathotypes. The presence of eaeA, stx(1), stx(2), and ehxA genes specific for the enterohemorrhagic E. coli (EHEC) pathotype was detected in 56%, 6%, 10%, and 13% of isolates, respectively. The VGs astA (69%) and aggR (29%), carried by enteroaggregative (EAEC) pathotypes, were frequently detected in E. coli isolates. The enteropathogenic E. coli (EPEC) gene bfp was detected in 24% of isolates. In addition, enteroinvasive E. coli (EIEC) VG ipaH was also detected in 14% of isolates. During dry periods, isolates belonging to the EAEC pathotype were most commonly detected (23%), followed by EHEC (11%) and EPEC (11%). Conversely, a more uniform prevalence of pathotypes, EPEC (14%), EAEC (12%), EIEC (10%), EHEC (7%), and ETEC (7%), was observed after the storm events. The results of this study highlight the widespread occurrence of potentially diarrheagenic pathotypes in the urban aquatic ecosystems. While the presence of VGs in E. coli isolates alone is insufficient to determine pathogenicity, the presence of diarrheagenic E. coli pathotypes in high frequency after the storm events could lead to increased health risks if untreated storm water were to be used for nonpotable purposes and recreational activities.